EFFECT OF MICRONUTRIENT NANOPARTICLES INJECTION AND SEAWEED EXTRACT APPLICATION ON SOME VEGETATIVE, CHEMICAL CHARACTERISTICS, AND YIELD OF APPLE TREES CV. IBRAHIMI - M. H. Hussien; R. M. Hamad (مجلة الأنبار للعلوم الزراعية)
The experiment was conducted in the village of Al-Bu-dhiyab, west of Ramadi during 16\3\2024 to 1\7\2024 spring season on 5-year-old Ibrahimi apple trees, to study the effects of injection micro-Nano elements and soil application of seaweed extract on vegetative growth, chemical properties, and yield. The experiment included three levels of injection: (0 - injection with distilled water only, B10+Fe20, and B20+Fe40 (mg L-1)) and the addition of seaweed extract at four concentrations: (0 soil application of pure water from distillation, 3, 6, and 9 ml. L-1). Treatments were applied in three batches on March 16, with a 20-day interval between each treatment. The following characteristics were studied: leaf area, total chlorophyll content, fruit set, fruit weight, fruit size, total yield, total sugar, total acidity, and pectin percentage in fruits.The findings indicated that the injectable therapy (B20+ (Fe40 mg L-1) resulted in a substantial enhancement of all examined features. Likewise, the incorporation of seaweed extract (9 ml L-1) resulted in an extensive improvement for examined attributes. The interaction between the study components revealed that the injectable therapy at the concentration of B20+(Fe40) and the addition of seaweed extracted with a level for 9 ml L-1 performed in all evaluated features